Island biogeography of the Macaronesian Gesnouinia and Mediterranean Soleirolia (Parietarieae, Urticaceae) with implications for the evolution of insular woodiness - Schüßler, Christina; Koch, Marcus (Taxon, 2019)
Urticaceae tribe Parietarieae serves as an excellent example to study hypotheses on Macaronesian‐​Mediterranean island biogeography. Parietarieae is distributed in both of these floristically closely...
Gesehen am 26.03.2020